Status Gizi dan Perkembangan Motorik Halus Anak Usia 48 – 60 Bulan - Prasetyowati Prasetyowati (Jurnal Kesehatan Metro Sai Wawai, 2018)
Background: Fine motor development in infants and young children is very important. Impaired motor coordination is known to affect 1 in 20 school-aged children. Objective: The study aims to describe the nutritional status and fine motor development of children aged 48-60 months in grade A students of PAUD Pertiwi Metro City. Methods: This study uses a descriptive design to describe the nutritional status and fine motor development of children aged 48-60 months. The study population was students of class A PAUD Pertiwi Metro City with a sample of 50 people. The sampling technique uses accidental sampling. Results: The results showed a picture of 12% of children with underweight nutritional status, there were 6% of children with normal motor development. There are children with normal nutritional status of 93.2% with normal fine motor development. Conclusion: The study concluded that the nutritional status of children has a tendency to support fine motor development in children aged 48 - 60. It is necessary for the school to collaborate with parents to monitor children's nutritional status and motor development routinely so that children can pass each developmental task according to their age.